HISTORY OF AUSTRALIAN BANKING - Jakaria, Saleh Ahmed (Australian Finance & Banking Review, 2023)
This paper offers a detailed exploration of the intricate history of Australian banking, unraveling its inception, progression, and pivotal junctures that have sculpted the financial terrain of the nation. Originating as modest colonial endeavors, Australian banks have evolved into significant players in the global financial arena. This journey of Australian banking mirrors a captivating fusion of economic dynamics, political frameworks, and societal shifts. By meticulously scrutinizing critical junctures, regulatory shifts, technological innovations, and socio-economic determinants, this paper endeavors to furnish a nuanced comprehension of the trajectory of Australian banking across centuries. From the pioneering ventures of the colonial era to the contemporary complexities of a digitalized world, the narrative unfolds a narrative rich in resilience, adaptation, and evolution. Through this examination, we gain insight into the enduring legacy, challenges, and transformative potential of Australian banking, illuminating its integral role in shaping the economic landscape of the continent. JEL Classification Codes: E50.